2014
DOI: 10.1186/1476-4598-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of prostate cancer and melanoma cells in a preclinical in vivo mouse model is enhanced by L-plastin expression and phosphorylation

Abstract: BackgroundTumor cell migration and metastasis require dynamic rearrangements of the actin cytoskeleton. Interestingly, the F-actin cross-linking and stabilizing protein L-plastin, originally described as a leukocyte specific protein, is aberrantly expressed in several non-hematopoietic malignant tumors. Therefore, it has been discussed as a tumor marker. However, systematic in vivo analyses of the functional relevance of L-plastin for tumor cell metastasis were so far lacking.MethodsWe investigated the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…This protein is an actin filament cross-linker that has been shown to contribute to the fine-tuning of actin turnover in breast cancer cells, and its phosphorylation by PKC-delta has recently been shown to induce actin polymerization and tumor cell invasion (72). The expression of LCP1 enhances metastatic properties in both prostate cancer and melanoma cells (73) and this study indicates a potential link with brain metastasis as well.…”
Section: Discussionmentioning
confidence: 62%
“…This protein is an actin filament cross-linker that has been shown to contribute to the fine-tuning of actin turnover in breast cancer cells, and its phosphorylation by PKC-delta has recently been shown to induce actin polymerization and tumor cell invasion (72). The expression of LCP1 enhances metastatic properties in both prostate cancer and melanoma cells (73) and this study indicates a potential link with brain metastasis as well.…”
Section: Discussionmentioning
confidence: 62%
“…While LPL is not normally expressed outside cells of the immune system, over half of epithelial carcinomas and non-epithelial mesenchymal tumors examined ectopically expressed LPL (Delanote et al, 2005). Moreover, phosphorylation of LPL is associated with metastasis (Riplinger et al, 2014), and variant alleles of LPL have been associated with cancer progression (Ning et al, 2014). Recently, it has been shown that depletion of LPL can inhibit tissue invasion by prostate cancer cell lines, and ectopic expression of LPL can increase the metastatic potential of melanoma lines (Riplinger et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, phosphorylation of LPL is associated with metastasis (Riplinger et al, 2014), and variant alleles of LPL have been associated with cancer progression (Ning et al, 2014). Recently, it has been shown that depletion of LPL can inhibit tissue invasion by prostate cancer cell lines, and ectopic expression of LPL can increase the metastatic potential of melanoma lines (Riplinger et al, 2014). Macrophage podosomes resemble cancer cell invadopodia in certain ways, so improved understanding of the function of LPL in podosome biology may reveal new targets for prevention of cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The L‐plastin isoform, which is abundantly expressed in hematopoietic cell lineages, is not active in most normal cells, but it is frequently activated and overexpressed in various types of human malignant solid tumors . The major functional domains of L‐plastin are two calcium‐binding sites, a calmodulin‐binding site, and two tandem actin‐binding domains . In vitro studies have indicated that L‐plastin is capable of bundling actin filaments through its actin‐binding domains and is regulated by phosphorylation of Ser5 .…”
mentioning
confidence: 99%
“…We have previously reported that L‐plastin expression is upregulated by both estrogen and androgen exposure in a steroid‐hormone sensitive prostate cancer model and is associated with the malignant state in prostatic epithelial cells . Overexpression of L‐plastin was shown to be functionally involved in prostate cancer invasion and metastasis both in vitro and in vivo . However, hormone‐free cultured LNCaP cells and androgen‐insensitive prostate cancer cells (PC‐3) presented overexpression of the L‐plastin gene, suggesting that other non‐steroidal factors might promote its expression.…”
mentioning
confidence: 99%